2017
DOI: 10.3390/languages2020003
|View full text |Cite
|
Sign up to set email alerts
|

Language Mixing and Diachronic Change: American Norwegian Noun Phrases Then and Now

Abstract: This article investigates the diachronic development of language mixing within noun phrases in the heritage language American Norwegian. By comparing data collected in the 1930s and 1940s with recently collected data, I present and discuss patterns showing systematic changes, specifically concerning the categories number and definiteness. Moreover, I propose two potential analyses of these patterns based on an exoskeletal approach to grammar. This theoretical framework crucially separates the abstract syntacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 58 publications
(120 reference statements)
1
45
0
Order By: Relevance
“…Successful acquisition of a second grammar in sequential bilinguals requires inhibiting L1 representations and allowing L2 representations to surface. Evidence of code-switching in heritage grammars (such as in American Norwegian: see Riksem, 2017) further supports this architecture. Potentially weaker representations may appear to be reduced (or ‘shrunken’), but the culprit is the failure to properly inhibit the dominant L2.…”
mentioning
confidence: 90%
“…Successful acquisition of a second grammar in sequential bilinguals requires inhibiting L1 representations and allowing L2 representations to surface. Evidence of code-switching in heritage grammars (such as in American Norwegian: see Riksem, 2017) further supports this architecture. Potentially weaker representations may appear to be reduced (or ‘shrunken’), but the culprit is the failure to properly inhibit the dominant L2.…”
mentioning
confidence: 90%
“…The research questions addressed are the following: First, in syntactic environments where English and EurNo differ in terms of using bare nouns versus nouns with an indefinite article, which patterns are preferred by AmNo speakers? Previous studies of AmNo have observed syntactic variation and change both in the verbal and nominal domain (e.g., Eide and Hjelde 2015;Larsson and Johannessen 2015;Westergaard and Andersen 2015;Riksem 2017;, but to date, the distribution of bare nouns versus nouns with an indefinite article has not been systematically investigated. An interesting comparative backdrop is formed by Hasselmo's (1974) and Heegård Petersen's (2018) observations from American Swedish and American Danish, which indicate some English-like use of articles in these varieties.…”
Section: Introductionmentioning
confidence: 97%
“…Riksem (2017) discusses two ways in which these patterns can be analyzed: (i) the syntactic structure is intact, and the changes are due to a change in the morphophonological exponents, (ii), the syntactic structure itself may have changed. The former analysis relies on a model within second language acquisition called the Missing Surface Inflection Hypothesis (MSIH), proposed by Lardiere (2000) and Prévost and White (2000).…”
mentioning
confidence: 99%
“…A fundamental claim is that a learner would rather omit a form than produce the wrong form (Lardiere, 2000), which again aligns with Polinsky and Scontras. However, as Riksem discusses (2017, p. 21), the MSIH does not make clear predictions concerning where and how inflection may go missing, making it possible for avoidance to explain any instance where the syntax and the morphophonology do not align according to a given baseline. Riksem (2017) favors the second hypothesis whereby the syntactic structure itself is the culprit for the diachronic changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation